Cryopreservation of Hamilin sweet orange [(Citrus sinensis (L.) Osbeck)] embryogenic calli using a modified aluminum cryo-plate technique - Duarte Souza, F.V.; Kaya, E.; Vieira, L.J.; Silva Souza, A.; Silva Carvalho, M.J.; Barbosa Santos, E.; Cunha Alves, A.A.; Ellis, David (Elsevier, 2017)
A modified aluminum cryo-plate technique was applied for cryopreservation of embryogenic citrus calli using aluminum cryo-plate. After encapsulation in a medium with 3% alginate, the beads were placed directly on aluminum foil troughs for exposure to plant vitrification solution (PVS2) incubated on ice for three intervals (30, 45 and 60 min). After rewarming, the calli were incubated under light (16 h/8 h) or dark at 27 ± 2 °C. The survival rates ranged from 59.2% following 45 min of PVS2 exposure to 88.7% after 30 min of exposure. The 30-min PVS2 treatment yielded the highest callus growth (1.4) and percentage of calli with embryos regenerated (43.57%). The highest percentage of embryos regenerated was observed in dark condition (75.2%). The method described using aluminum foil troughs is efficient for cryopreservation of embryogenic citrus calli.